Faktor-Faktor Penentu Akuntabilitas Kinerja Pemerintah: Dari Anggaran hingga Sistem Pelaporan - Zanabel Nuriajan Tauda; Gregorius Jeandry; Sheila Kusumaningrum; Zainuddin Zainuddin (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to analyze the influence of performance-based budgeting, government internal control systems, compliance with laws and regulations, human resource competence, and reporting systems on the performance accountability of government agencies in Ternate City. A quantitative approach was employed using a survey method. Data were collected through questionnaires distributed to 120 respondents from 34 Regional Apparatus Organizations (OPD) selected using purposive sampling. Data were analyzed using multiple linear regression with SPSS. The results reveal that performance-based budgeting and internal control systems have a positive and significant effect on performance accountability. In contrast, compliance with regulations, human resource competence, and reporting systems do not have a significant influence. The model explains 63% of the variance in the dependent variable. The novelty of this research lies in the simultaneous testing of five variables affecting accountability, particularly the inclusion of the reporting system, which has rarely been examined alongside other factors in the context of local governments. These findings emphasize the importance of implementing results-oriented budgeting and effective internal controls to enhance government accountability..